Identifying the causes and consequences of pregnancy in Iranian Kurdish women under the age of 18: A grounded theory study - Javad Yoosefi lebni; Ahmad Ahmadi; Seyed Fahim Irandoost; Mandana Saki; Hossein Safari; Nafiul Mehedi (Heliyon)
Background: Since teenage pregnancy is one of the major challenges for healthcare systems worldwide and can pose risks to the health of young mothers and their infants, the present study was conducted to identify the Identifying the causes and consequences of pregnancy in Iranian Kurdish women under the age of 18. Method: The present qualitative research was conducted using the grounded theory method among women with experience of pregnancy under the age of 18 and key informants who had experience and knowledge in this field. Data were collected through semi-structured face-to-face interviews with 26 women and 17 key informants who were selected through purposive, snowball, and theoretical sampling methods. Sampling continued until theoretical saturation. The data were collected and analyzed for 8 months, from November 2021 to June 2022. Data analysis was performed based on the approach of Strauss and Corbin in the MAXQDA-2018 software environment. The Guba and Lincoln criteria were observed to ensure the trustworthiness of the data and results. Results: After the data analysis and coding process, the conceptual model of causes and consequences of pregnancy in adolescents emerged, including 1) predisposing conditions (sociocultural factors: Social learning, misconceptions about fertility and childbirth, preventing stigma), 2) causal conditions (individual factors: lack of knowledge on how to prevent pregnancy, improper use of contraceptives, inadequate knowledge about the risks of pregnancy in adolescence, fear of the side effects of using contraceptives, filling the vacuum of loneliness, family factors: husband's and his family's pressure, committing her husband to life, consolidating her position in family), 3) intervening conditions (structural factors: no barriers to pregnancy, difficult access to contraceptives), 4) strategies and interactions (positive reactions: trying to prepare herself for raising a child, taking better care of herself and her child, negative reactions: trying to kill herself and the kid, fear and concealment), and 5) consequences (destructive consequences: threats to the health of the child, threat to mother's health, inadequate access to health services, constructive consequences: increase of support, strengthen the sense of empowerment). Conclusion: Pregnancy in adolescence is influenced by socio-cultural, family, personal, and structural factors that can lead to positive and negative consequences for women, which in most cases make the lives and health of them and their children difficult. The findings of the study can be used in the areas of health and social policy, program planning, and designing interventions and educational programs aimed at changing beliefs and cultural attitudes related to pregnancy under the age of 18 at the individual, family, and societal levels.